Ultrathin and Non‐Flammable Dual‐Salt Polymer Electrolyte for High‐Energy‐Density Lithium‐Metal Battery. (23rd February 2021) - Lin, Xidong; Yu, Jing; Effat, Mohammed B.; Zhou, Guodong; Robson, Matthew J.; Kwok, Stephen C. T.; Li, Haijun; Zhan, Shiying; Shang, Yongliang; Ciucci, Francesco
Abstract: Rechargeable batteries with Li‐metal anodes and Ni‐rich LiNi x Mn y Co z O2 ( x + y + z = 1, NMC) cathodes promise high‐energy‐density storage solutions. However, commercial carbonate‐based electrolytes (CBEs) induce deteriorative interfacial reactions to both Li‐metal and NMC, leading to Li dendrite formation and NMC degradation. Moreover, CBEs are thermally unstable and flammable, demonstrating severe safety risks. In this study, an ultrathin and non‐flammable dual‐salt polymer electrolyte (DSPE) is proposed via lightweight polytetrafluoroethylene scaffold, poly(vinylidene fluoride‐ co ‐hexafluoropropylene) polymeric matrix, dual‐salt, and adiponitrile/fluoroethylene carbonate functional plasticizers. The as‐obtained DSPE exhibits an ultralow thickness of 20 µm, high room temperature ionic conductivity of 0.45 mS cm −1, and a large electrochemical window (4.91 V versus Li/Li + ). The dual‐salt synergized with functional plasticizers is used to fabricate a stable interface layer on both anode and cathode. In‐depth experimental and theoretical analyses have revealed the formation of stable interfaces between the DSPE and the anode/cathodes. As a result, the DSPE effectively prevents Li/DSPE/Li symmetric cell from short‐circuiting after 1200 h, indicating effective suppression of Li dendrites. Moreover, the Li/DSPE/NMC cell delivers outstanding cyclic stability at 2 C, maintaining a high capacity of 112 mAh g −1 over 1000 cycles. Abstract : Li‐metal batteries with Ni‐rich LiNi x Mn y Co z O2 (NMC) cathodes promise high‐energy‐density storage solutions. However, commercial carbonate‐based electrolytes (CBEs) induce deteriorative interfacial reactions to both Li‐metal and NMC, leading to Li dendrites and NMC degradation. Moreover, CBEs are flammable, demonstrating severe safety risks. Therefore, an ultrathin and non‐flammable dual‐salt polymer electrolyte is fabricated for Li/NMC battery with high‐safety and excellent electrochemical performance.